Ankle and Hindfoot Symptoms after Medial Open Wedge High Tibial Osteotomy - Shah, Siddharth Mahesh; Roberts, Jason; Picard, Frederic (The Journal of Knee Surgery, 2019)
Medial open wedge high tibial osteotomy (MOWHTO) is a commonly performed procedure for symptomatic medial compartment osteoarthritis (OA). However, little is known about its effects on ipsilateral ankle or hindfoot. The aim of our study was to determine the incidence of ankle or hindfoot problems after MOWHTO and examine its association with radiological indices. Thirty-five knees (32 patients) undergoing navigated MOWHTO were evaluated for the presence of new-onset ankle or hindfoot symptoms after surgery. Pre- and postoperative hip-knee-ankle (HKA) angle, medial proximal tibial angle (MPTA), and tibial plafond inclination (TPI) were measured and compared on standing lower limb alignment radiographs. The mean postoperative change in HKA angle, MPTA, and TPI was 8.8°, 7.0°, and 8.4°, respectively. New-onset unexplained ankle or hindfoot symptoms were seen in 20% of the cases after surgery. Postoperative change in TPI was significantly greater in symptomatic patients as compared with asymptomatic ones (12.8° ± 4.9° vs. 8.1° ± 4.8°, p = 0.03). The odds ratio (OR) for developing ankle or hindfoot symptoms in cases with ≥ 10° change in TPI postoperatively was 10.8 (p = 0.04). Ankle or hindfoot symptoms were successfully managed with conservative treatment in all cases.
Keywords: high tibial osteotomy; open wedge; navigated; tibial plafond inclination; ankle joint line obliquity